(untitled) - Jansen, Marius B. (Stanford, Calif., 1971)
Jansen's book is built around the figure of Sakamoto Ryoma, one of the most fascinating though neglected of the young political activists who brought about the restoration. Through Sakamoto, jasen has given us a vivid picture of the uncertain course of Japanese politics from 1853-1868.